Efforts to Improve Appropriate Trauma Activation for Patients Transferred to a Level 1 Trauma Center From Outside Hospitals. Issue 5 (May 2020) - Seegert, Sara; Redfern, Roberta E.; Chapman, Bethany; Benson, Daniel
Trauma centers monitor under- and overtriage rates to comply with American College of Surgeons Committee on Trauma verification requirements. Efforts to maintain acceptable rates are often undertaken as part of quality assurance. The purpose of this project was to improve the institutional undertriage rate by focusing on appropriately triaging patients transferred from outside hospitals (OSHs). Trauma physicians received education and pocket cards outlining injury severity score (ISS) calculation to aid in prospectively estimating ISS for patients transferred from OSHs, and activate the trauma response expected for that score. Under- and overtriage rates before and after the intervention were compared. The postintervention period saw a significant decrease in overall overtriage rate, with simultaneous trend toward lower overall undertriage rate, attributable to the significant reduction in undertriage rate of patients transferred from OSHs. Prospectively estimating ISS to assist in determining trauma activation level shows promise in managing appropriate patient triage. However, questions arose regarding the necessity for full trauma activation for transferred patients, regardless of ISS. It may be necessary to reconsider how patients transferred from OSHs are evaluated. Full trauma activation can be a financial and resource burden, and should not be taken lightly.